Hugo Chávez and the building of his self-image through metaphor - Isabel Negro Alousque (Ibérica, 2015)
In the last decades metaphor has been much researched from both theoretical and empirical perspectives. One of the metaphor research lines has been the study of metaphor in specialized genres, including politics (Musolff, 2004). Political metaphor has been considerably researched within the cognitive framework and a few investigations have been concerned with the use of metaphor by political leaders (e.g. Semino & Masci, 1996; Charteris-Black, 2004, 2009). The present paper focuses on the use of metaphor in the public discourse of Hugo Chávez, the former Venezuelan president. Chávez was a captivating, if polarizing, leader whose hallmark was his oratory. We analyse a sample of Chávez’s speeches for evidence of its metaphorical content. We identify and explain the linguistic and conceptual metaphors that occur in his speeches with a view to demonstrating that they play a central role in the construction of Chávez’s self-image as both a political and religious leader for persuasive purposes.